2020
DOI: 10.22495/jgrv9i4art1
|View full text |Cite
|
Sign up to set email alerts
|

Environmental responsibility performance, corporate social responsibility disclosure, tax aggressiveness: Does corporate governance have a role?

Abstract: The self-assessment system tends to provide a loophole for companies to reduce tax payment. The great benefit of the tax to the community links tax with social responsibility. This study aims to investigate the effect of environmental responsibility performance and social responsibility disclosure on tax aggressiveness as well as the role of corporate governance in moderating these effects. The analysis in this study was conducted on 34 non-financial companies listed on the Indonesia Stock Exchange and were pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 89 publications
2
42
0
11
Order By: Relevance
“…Based on stakeholder theory, tax avoidance is not an ethical activity because taxes are a form of corporate responsibility as citizens who enjoy public facilities provided by the government through funds derived from taxes (Firmansyah and Estutik, 2020). Thus, we need a mechanism that aligns the interests of the company and the demands of investors so that the company behaves ethically.…”
Section: Theoretical Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on stakeholder theory, tax avoidance is not an ethical activity because taxes are a form of corporate responsibility as citizens who enjoy public facilities provided by the government through funds derived from taxes (Firmansyah and Estutik, 2020). Thus, we need a mechanism that aligns the interests of the company and the demands of investors so that the company behaves ethically.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…Therefore, a positive impression is more likely to emerge from companies that disclose their social responsibility than those that do not. (Firmansyah and Estutik, 2020) found that corporate social responsibility disclosure is negatively associated with tax aggressiveness.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Variabel independen yang digunakan dalam penelitian ini adalah tingkat pengungkapan keberlanjutan dengan menggunakan proksi indeks GRI 2018. Penggunaan proksi ini menyesuaikan dari proksi sebelumnya yang dilakukan oleh , Firmansyah & Estutik (2020), Firmansyah & Irwanto (2020), dan Widyansyah et al (2021), dengan melakukan penyesuaian ke dalam GRI 2018 dan kualitas pengungkapan. GRI 2018 membagi kriteria keberlanjutan menjadi 3 poin utama.…”
Section: Metodeunclassified